2020
DOI: 10.1186/s13584-020-00394-1
|View full text |Cite
|
Sign up to set email alerts
|

Associations between ethnicity, place of residence, hearing status of family and habilitation of children with hearing impairment

Abstract: Background Hearing parents tend to have a strong preference for their deaf and hard-of-hearing children to acquire adequate speech, as opposed to use of sign language. Research reports the contribution of many variables to speech acquisition by children with hearing loss (HL). Yet, little is known about the association between ethnicity, place of residence, and hearing status of family members and mode of communication of young people with HL. The purpose of the present study was to examine whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Lastly, based on the findings of previous studies, the present study identified various factors that could influence PES and ESS. Notably, key indicators such as ethnicity, economic status, area of living, and culture have not been thoroughly examined [ 107 ]. This suggests that the results of the included studies do not necessarily apply to Asian cultures or even multicultural Malaysians.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, based on the findings of previous studies, the present study identified various factors that could influence PES and ESS. Notably, key indicators such as ethnicity, economic status, area of living, and culture have not been thoroughly examined [ 107 ]. This suggests that the results of the included studies do not necessarily apply to Asian cultures or even multicultural Malaysians.…”
Section: Discussionmentioning
confidence: 99%